Corpus-Based Design of the "Social Media Research Dictionary" at UNIDA Gontor - Ashari, Maulana; Suryadarma, Yoke; Sofian, Ahmad Ario (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Corpus linguistics is a well-established field in language learning, studied by experts in the field, and has continued to develop significantly with the advancement of digital technology in the era of Industry 4.0. In Arabic language learning in Indonesia, the use of corpus linguistics remains low, as does its application in the development of bilingual Indonesian-Arabic dictionaries across various fields. However, the need for an Indonesian-Arabic bilingual dictionary is an ongoing necessity for Arabic learners in Indonesia, especially for non-native speakers. Based on this, this study aims to provide an overview of the design research for the Dictionary of Social Media Research as an Indonesian-Arabic bilingual dictionary in the field of Social Media Research, utilizing the SketchEngine application for corpus-based data processing and vocabulary development (entries and lemmas). This dictionary will be used by Communication Science students at UNIDA Gontor or other Arabic learners as a learning tool for Arabic. The research method used in this study is qualitative, providing a descriptive analysis through a corpus linguistic approach to the design of the Dictionary of Social Media Research as an Indonesian-Arabic. The study finds that the design of the Indonesian-Arabic bilingual dictionary using the corpus linguistic approach can be optimally executed, producing the most frequently used vocabulary in the field of social media research.